Terapi Komplementer Terhadap Tekanan Darah pada Penderita Hipertensi: Studi Literatur - Angger Anugerah; Ahmad Zainal Abidin; Joni Prastiyo (Journal of Bionursing, 2022)
Background. Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries, transporting blood from the heart and pumping it throughout the tissues and organs of the body continuously for more than one period. The use of complementary therapy has been widely used to accelerate the recovery of patients with hypertension. The purpose of this study was to analyze studies related to complementary therapy in hypertensive patients. Methods. The literature search was carried out in 3 databases, namely Google Scholar, SINTA and Pubmed. The research taken is research published in the last 10 years. The design of this study used the literature review method. The population of this study were all national and international journals related to complementary therapy in patients with hypertension. The sample in this study was 10 articles from international journals. Results. Based on the results of the search for journals, it can be concluded that, complementary therapy in this study found 5 types of approaches. These approaches include meditation, murotal, exercise, cucumber herbs, and cupping therapy. Conclusion. It is hoped that this literature study can provide additional information for health workers regarding the types and effectiveness of complementary therapies in patients with hypertension. Moreover, the results of this study can be used for further research to conduct more representative research.